Separator substrate for fuel cells
Patent Information
- Application Number
- JP2025064529
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-09
- Publication Date
- 2026-10-22
AI Technical Summary
【0006】 本願発明の発明者らは、不働態皮膜の表面が複数のピットを有すると、セパレータ基材の接触抵抗が有意に低減されることを見出した。そして、この知見に基づいて鋭意研究を重ねた結果、当該表面の算術平均粗さ(Ra)と、ピットの平均深さとが、それぞれ上記した範囲内にある場合に、接触抵抗が十分に低減されることを見出した。このセパレータ基材を燃料電池に採用することで、燃料電池の発電効率の向上を図ることができる。
Smart Images

Figure 2026170753000001_ABST
Abstract
Description
[Technical Field]
[0001] The technology disclosed herein relates to separator substrates for fuel cells. [Background technology]
[0002] Patent Document 1 describes a separator substrate for fuel cells. This separator substrate is made of stainless steel having a passivation film. Regarding the passivation film, it is stated that the average spacing of local peaks in the surface roughness curve is 0.3 μm or less. [Prior art documents] [Patent Documents]
[0003] [Patent Document 1] Patent No. 5109234 [Overview of the project] [Problems that the invention aims to solve]
[0004] As described above, in separator substrates made of stainless steel, the contact resistance of the separator substrate can be reduced by modifying the passivation film. This specification also provides a new technique for reducing the contact resistance of a separator substrate by modifying the passivation film. [Means for solving the problem]
[0005] The technology disclosed herein is embodied in a separator substrate for fuel cells. In a first embodiment, the separator substrate is made of a stainless steel material having a passivation film. Multiple pits are formed on the surface of the passivation film. The arithmetic mean roughness (Ra) of the surface is 6 nm or more and 18 nm or less. The average depth of the pits is 20 nm or more and 100 nm or less.
[0006] The inventors of the present invention have found that when the surface of a passive film has multiple pits, the contact resistance of the separator substrate is significantly reduced. Based on this finding, they conducted further research and found that the contact resistance is sufficiently reduced when the arithmetic mean roughness (Ra) of the surface and the average depth of the pits are both within the above-mentioned ranges. By using this separator substrate in a fuel cell, the power generation efficiency of the fuel cell can be improved.
[0007] In a second embodiment, the F / Fe ratio in the passivation film may be 0.01 or greater, in the first embodiment. Here, F is fluorine and Fe is iron. The amounts of F and Fe are both at% (atomic percent). F acts as an electron carrier. Therefore, by setting the F / Fe ratio in the passivation film to 0.01 or greater, the contact resistance of the passivation film can be sufficiently reduced. [Brief explanation of the drawing]
[0008] [Figure 1] A diagram schematically showing the configuration of the separator substrate 10 of the embodiment. [Figure 2] Figure 2(A) is an example of an SEM image of the surface of the separator substrate of the example, and Figure 2(B) is an example of an SEM image of the surface of the separator substrate of the comparative example. [Figure 3] Figure 3(A) is an example of a TEM image of the cross-section of the separator substrate of the example, and Figure 3(B) is an example of a TEM image of the cross-section of the separator substrate of the comparative example. [Figure 4] Figure 4(A) shows the relationship between the average pit depth and the F / Fe ratio, and Figure 4(B) shows the relationship between the arithmetic mean roughness (Ra) of the surface and the F / Fe ratio. [Modes for carrying out the invention]
[0009] The separator substrate 10 of this embodiment will be described with reference to the drawings. The separator substrate 10 of this embodiment has a plate shape. A fuel cell separator can be manufactured by forming through holes and / or grooves in the separator substrate 10 of this embodiment. The separator substrate 10 is made of stainless steel. Examples of stainless steel materials include austenitic stainless steel, ferritic stainless steel, martensitic stainless steel, and austenitic-ferritic (duplex) stainless steel. Specific examples of stainless steel materials include SUS301, SUS304, SUS316, SUS430, SUS430J1L, SUS434, SUS444, and SUS631. The thickness of the separator substrate 10 is not particularly limited, but for example, it is 0.05 mm or more and 0.3 mm or less.
[0010] As shown in Figure 1, the separator substrate 10 comprises a substrate body 12 and a passivation film 14. The passivation film 14 is provided on the surface of the substrate body 12 (in this case, the surface in the +Y direction). The thickness of the passivation film 14 is not particularly limited, but for example, it is 0.1 nm or more and 20 nm or less.
[0011] As shown in Figure 1, the passivation film 14 has a plurality of pits 16. Each of the plurality of pits 16 is a depression with a substantially circular opening. The diameter of the opening of each pit 16 is not particularly limited, but for example, it is between 25 nm and 200 nm. The plurality of pits 16 are formed on the surface of the passivation film 14 (here, the plane in the +Y direction). The plurality of pits 16 are irregularly distributed on the surface of the passivation film 14. The portion of the surface of the passivation film 14 where no pits 16 are formed is a substantially flat surface.
[0012] The plurality of pits 16 have different depths. The depth as used herein refers to the distance from the surface of the passivation film 14 to the deepest position of the pits 16. The average depth of the plurality of pits 16 is, for example, 20 nm or more and 100 nm or less, for example, 25 nm or more and 90 nm or less, and for example, 30 nm or more and 80 nm or less. The average depth of the plurality of pits 16 is calculated, for example, as the average value of the measured depths of the plurality of pits 16 in a cross section observed with a Transmission Electron Microscope (TEM). However, the plurality of pits 16 may have the same depth.
[0013] The arithmetic mean roughness (Ra) of the surface of the passivation film 14 is, for example, 6 nm or more and 18 nm or less, and for example, 10 nm or more and 16 nm or less. Here, the arithmetic mean roughness (Ra) is defined in JIS B 0601:2013. The arithmetic mean roughness (Ra) can be calculated based on a surface roughness curve measured using, for example, an Atomic Force Microscope (AFM).
[0014] The F / Fe ratio in the passivation film 14 is not particularly limited, and is, for example, 0.01 or more, for example, 0.02 or more, and for example, 0.05 or more. The F / Fe ratio in the passivation film 14 is calculated based on the F content and the Fe content in the passivation film 14 measured by, for example, X-ray Photoelectron Spectroscopy (XPS). The F content in the passivation film 14 is, for example, 0.5 at% or more and 5.0 at% or less, and the Fe content in the passivation film 14 is, for example, 5.0 at% or more and 15.0 at% or less.
[0015] The inventors of the present application have found that when the surface of the passivation film 14 has a plurality of pits 16, the contact resistance of the separator substrate 10 is significantly reduced. As a result of extensive research based on this finding, the inventors have found that, as in the above-described embodiment, when the arithmetic mean roughness (Ra) of the surface is 6 nm or more and 18 nm or less, and the average depth of the pits is 20 nm or more and 100 nm or less, the contact resistance is sufficiently reduced. By employing this separator substrate 10 in a fuel cell, the power generation efficiency of the fuel cell can be improved.
[0016] Although it is merely an example, the F / Fe ratio in the passivation film 14 is 0.01 or more. F serves as an electron carrier. Therefore, by setting the F / Fe ratio in the passivation film 14 to 0.01 or more, the contact resistance of the passivation film 14 can be sufficiently reduced.
[0017] Next, a method for manufacturing the separator substrate 10 of the embodiment will be described. In this manufacturing method, the passivation film 14 of the plate-shaped stainless steel material is modified.
[0018] The manufacturing method includes a first step of subjecting the separator substrate 10 to heat treatment. In the first step, the heat treatment is performed in the atmosphere or in an inert gas atmosphere such as nitrogen or Ar. The temperature at this time is, for example, 100°C or higher and 700°C or lower. The heat treatment time is, for example, 30 seconds or more and 30 minutes or less.
[0019] The manufacturing method further includes a second step of implanting fluorine into the passivation film 14. In the second step, the stainless steel material heat-treated in the first step is subjected to pulse electrolysis in an aqueous solution containing fluoride ions. Thereby, an anode potential and a cathode potential are alternately applied to the stainless steel material. The anode current density is, for example, 0.05 A / dm 2 or more and 1.0 A / dm 2 or less. The cathode current density is, for example, 0.05 A / dm 2 or more and 5.0 A / dm 2The following applies: The pulse electrolysis time is, for example, 10 seconds or more and 10 minutes or less. Here, the pulse electrolysis time is the sum of the anode pulse time and the cathode pulse time. The anode pulse time is the time for which the anode potential is applied, and the cathode pulse time is the time for which the cathode potential is applied. Each of the anode pulse time and the cathode pulse time can be arbitrarily changed within the range of the pulse electrolysis time. Note that in pulse electrolysis, the potential applied first may be the anode potential or the cathode potential.
[0020] The fluoride ion source for fluorine injection is not limited to hydrofluoric acid or any fluorine compound that dissolves in water to produce fluoride ions; any compound can be used. Examples of fluoride ion sources include alkali metal fluorides such as sodium fluoride and potassium fluoride, ammonium fluoride, antimony trifluoride, copper fluoride, sodium hydrogen difluoride, and potassium hydrogen difluoride. The pH of the aqueous solution containing fluoride ions is, for example, between 0 and 3. The concentration of fluoride ions in the aqueous solution is, for example, 0.001 kmol / m³. 3 The concentration is above and below the saturation concentration. The temperature of the aqueous solution containing fluoride ions is, for example, between 10°C and 30°C.
[0021] The manufacturing method further comprises a third step of modifying the passivation film 14 in an alkaline aqueous solution or a non-aqueous solvent. In the third step, the stainless steel material that was pulse-electrolyzed in the second step is pulse-electrolyzed in an alkaline aqueous solution or a non-aqueous solvent. As a result, an anode potential and a cathode potential are alternately applied to the stainless steel material. The anode current density and the cathode current density are, for example, 0.001 A / dm². 2 The above and 10A / dm 2It is as follows. The pulse electrolysis time is, for example, 5 seconds or more and 10 minutes or less. Each of the anode pulse time and the cathode pulse time can be arbitrarily changed within the range of the pulse electrolysis time. In pulse electrolysis, the potential applied first may be an anode potential or a cathode potential. However, in the third step, instead of pulse electrolysis, anodic electrolysis in which only the anode potential is applied may be adopted.
[0022] Examples of the alkaline aqueous solution include a sodium hydroxide solution, a potassium hydroxide solution, a calcium hydroxide solution, a magnesium hydroxide solution, a barium hydroxide solution, a lithium hydroxide solution, an ammonium hydroxide solution, and the like. Examples of the non-aqueous solvent include ethanol, methanol, dimethyl ether, diethyl ether, methyl ethyl ether, and the like. Alternatively, a mixed solution of water and a water-miscible non-aqueous solvent may be used. The pH of the alkaline aqueous solution is, for example, 10 or more. The temperature of the alkaline aqueous solution or the non-aqueous solvent is 10°C or more and 30°C or less.
[0023] The production method further includes a fourth step of eluting iron in the passive film 14. In the fourth step, the stainless steel material that has been subjected to pulse electrolysis in the third step is immersed in an aqueous solution containing fluoride ions. Examples of the aqueous solution containing fluoride ions include hydrofluoric acid, or an aqueous solution obtained by adding an acid to the aforementioned fluoride ion source to make it acidic. The pH of the aqueous solution containing fluoride ions is, for example, 0 or more and 3 or less. The concentration of fluoride in the aqueous solution is, for example, 0.001 kmol / m 3 or more and a saturation concentration or less. Examples of the acid for pH adjustment include nitric acid, sulfuric acid, phosphoric acid, and the like. The concentration of the acid for pH adjustment in the aqueous solution is, for example, 0.01 kmol / m 3 or more and 10 kmol / m 3 or less. The temperature of the aqueous solution containing fluoride ions is, for example, 10°C or more and 80°C or less. The immersion time is, for example, 5 seconds or more and 20 minutes or less.
[0024] According to the manufacturing method described above, multiple pits 16 having an average depth of 20 nm or more and 100 nm or less can be formed in the passive film 14 of the stainless steel material. Furthermore, these pits 16 result in an arithmetic mean roughness (Ra) of the surface of the passive film 14 being 6 nm or more and 18 nm or less. Therefore, the separator substrate 10 of this embodiment can be manufactured by the manufacturing method described above.
[0025] The following describes examples of this technology, but it is not intended to limit this technology to those shown in these examples.
[0026] (Example 1) In Example 1, as shown in Table 1, first, as the first step, SUS304 stainless steel (plate thickness: 0.2 mm) was heated in air at 550°C for 1 minute. As the second step, the SUS304 was pulse-electrolyzed for 60 seconds in a 5 mass% HF aqueous solution. At this time, both the anode current density and cathode current density were 0.36 A / dm². 2 As the third step, the SUS304 was processed at 1 kmol / m³ 3 The system was further pulsed in an aqueous LiOH solution for 10 seconds. At this time, both the anode current density and the cathode current density were 1.0 A / dm². 2 Finally, as the fourth step, the SUS304 was immersed in a 5% by mass HF aqueous solution for 10 seconds to produce the separator substrate 10 of Example 1.
[0027] [Table 1]
[0028] (Example 2) As shown in Table 1, in Example 2, instead of the 10-second pulse electrolysis using the LiOH aqueous solution in Example 1, 1 kmol / m³ 3 Anode electrolysis was performed in an aqueous LiOH solution for 5 seconds. Except for this point, Example 2 is the same as Example 1.
[0029] (Example 3) As shown in Table 1, in Example 3, the cathode current density in pulse electrolysis using the HF aqueous solution of Example 1 was 3.0 A / dm². 2 The following changes were made. In addition, the pulse electrolysis time using the LiOH aqueous solution in Example 1 was changed to 60 seconds. Furthermore, instead of heating at 550°C for 1 minute in Example 1, heating at 500°C for 5 minutes was performed. Except for these points, Example 3 is the same as Example 1.
[0030] (Example 4) As shown in Table 1, in Example 4, compared to Example 3, the anode current density and cathode current density in pulse electrolysis using an aqueous LiOH solution were both 3.0 A / dm². 2 This was changed. Except for this point, Example 4 is the same as Example 3.
[0031] (Example 5) As shown in Table 1, in Example 5, compared to Example 3, the anode current density and cathode current density in pulse electrolysis using an aqueous LiOH solution were both 0.01 A / dm². 2 This was changed. Except for this point, Example 5 is the same as Example 3.
[0032] (Comparative Example 1) As shown in Table 1, in Comparative Example 1, the anode current density and cathode current density in pulse electrolysis using the HF aqueous solution of Example 1 were 0.004 A / dm², respectively. 2 The following changes were made. In addition, the pulse electrolysis time using the LiOH aqueous solution in Example 1 was changed to 20 seconds. Aside from these points, Comparative Example 1 is the same as Example 1.
[0033] (Comparative Example 2) As shown in Table 1, in Comparative Example 2, the pulse electrolysis time using the LiOH aqueous solution from Comparative Example 1 was changed to 20 seconds. Except for these points, Comparative Example 2 is the same as Comparative Example 1.
[0034] (Comparative Example 3) As shown in Table 1, in Comparative Example 3, the anode current density in pulse electrolysis using the HF aqueous solution of Example 3 was 0.18 A / dm². 2 This was changed. Except for this point, Comparative Example 3 is the same as Example 3.
[0035] (Comparative Example 4) As shown in Table 1, Comparative Example 4 is SUS304 used as the stainless steel material. That is, Comparative Example 4 is SUS304 that has not undergone any treatment.
[0036] (Arithmetic mean roughness) Using an atomic force microscope, the arithmetic mean roughness (Ra) of the passivation film surface of the separator substrate in each example was measured under the following conditions. The surface of the passivation film on the separator substrate in each example was scanned longitudinally (i.e., in the Z direction) at three different locations to obtain three surface roughness curves. Similarly, the same surface was scanned transversely (i.e., in the X direction) at three different locations to obtain three surface roughness curves. For each of these six surface roughness curves, flattening was performed using Flatten and Plane Fit filters. The average value of the surface roughness at the scanned distance was then calculated, and this average value was defined as the arithmetic mean roughness (Ra). The results are shown in Table 2. • Device name: Bruker Dimension Icon • Measurement conditions: Tapping mode • Scan speed: 0.8Hz • Measurement points: 512 x 512 points
[0037] (Average depth of the pit) The surface of each separator substrate was pre-treated using a focused ion beam (FIB) system. The surface of each separator substrate was observed using a scanning transmission electron microscope (STEM) in five different fields of view under the conditions described below (see Figure 2). In each field of view, the separator substrate was cut in the thickness direction at an arbitrary point, and the cross-section was observed using TEM (see Figure 3). The depth of multiple pits in the TEM image of each cross-section was measured, and the average value was calculated as the average pit depth. The results are shown in Table 2. • Device name: Hitachi High-Tech HD-2700 • Acceleration voltage: 200kV • Observation mode: ZC image ·Magnification: 50000x
[0038] (F / Fe ratio) Under the conditions described below, the amount of F (at%) and Fe (at%) in the passivation film of each separator substrate was measured, and the F / Fe ratio in the passivation film was calculated. The results are shown in Table 2. • Equipment: ULVAC-FI PHI5000VersaProbe II ·Analysis area: 200×1400μm • X-ray source: Monochromatic AlKα (1486.6 eV) • Photoelectron escape angle: 90° (normal direction to the sample) • Charge-up correction: C1s 285eV (hydrocarbons)
[0039] (contact resistance) Samples for measurement were prepared by cutting the separator substrate of each example into 15 mm x 50 mm pieces. The initial and post-duration contact resistance of each sample was measured under the conditions described below. The initial contact resistance is the contact resistance measured first after the sample was prepared. The post-duration contact resistance is the contact resistance measured after immersing the prepared sample in an FCC solution (ethylene glycol:water = 50:50) and leaving it at 85°C for 1000 hours. The results are shown in Table 2. • Equipment: Electrical contact simulator (CRS-113-Mold), manufactured by Yamazaki Seiki Kenkyusho Co., Ltd. • Measuring probe: PU-05 gold wire contact, 0.5mmΦ ·Applied constant current: 10mA
[0040] [Table 2]
[0041] The results shown in Table 2 indicate that, in the separator substrate, contact resistance is sufficiently reduced both initially and after durability when the arithmetic mean roughness (Ra) of the passivation film surface is 6 nm or more and 18 nm or less, and the average depth of the pits formed on the surface is 20 nm or more and 100 nm or less.
[0042] In addition, as shown in Table 2 and Figures 4(A)-4(B), it was found that when the F / Fe ratio in the passivation film is 0.01 or higher, the contact resistance is sufficiently reduced both initially and after durability. This is thought to be because there is a relatively large amount of F, which acts as an electron carrier, in the passivation film.
[0043] The manufacturing method described above does not necessarily have to include the first step. Furthermore, in the manufacturing method described above, the third step may be performed before the second step. In addition to or instead of this, the second and third steps may be repeatedly performed in the manufacturing method described above.
[0044] Although several specific examples have been described in detail above, these are merely illustrative and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes to the specific examples illustrated above. The technical elements described in this specification or in the drawings exhibit technical usefulness individually or in combination. [Explanation of Symbols]
[0045] 10: Separator substrate, 12: Substrate body, 14: Passivation film, 16: Pit
Claims
1. A separator substrate for fuel cells, It is made of stainless steel material having a passivation film, Multiple pits are formed on the surface of the aforementioned passivated film. The arithmetic mean roughness (Ra) of the surface is 6 nm or more and 18 nm or less. The average depth of the pit is 20 nm or more and 100 nm or less. Separator substrate.
2. The separator substrate according to claim 1, wherein the F / Fe ratio in the passivated film is 0.01 or more.
Citation Information
Patent Citations
Batsuteriodengentosuru inbaatakairo
JP1976009234A